Fracture toughness evaluation of NiAl single crystals by microcantilevers—a new continuous J-integral method. Issue 23 (7th November 2016) - Ast, Johannes; Merle, Benoit; Durst, Karsten; Göken, Mathias
Abstract: Abstract : The fracture toughness of NiAl single crystals is evaluated with a new method based on the J-integral concept. The new technique allows the measurement of continuous crack resistance curves at the microscale by continuously recording the stiffness of the microcantilevers with a nanoindenter. The experimental procedure allows the determination of the fracture toughness directly at the onset of stable crack growth. Experiments were performed on notched microcantilevers which were prepared by focused ion beam milling from NiAl single crystals. Stoichiometric NiAl crystals and NiAl crystals containing 0.14 wt% Fe were investigated in the so-called "hard" orientation. The fracture toughness was evaluated to be 6.4 ± 0.5 MPa m 1/2 for the stoichiometric sample and 7.1 ± 0.5 MPa m 1/2 for the iron containing sample, indicating that the addition of iron enhances the ductility. This effect is intensified with ongoing crack propagation where the Fe-containing sample exhibits a stronger crack resistance behavior than the stoichiometric NiAl single crystal. These findings are in good agreement with macroscopic fracture toughness measurements, and validate the new micromechanical testing approach.